In vitro anti-angiogenic properties of ethanolic crude extract of Vernonia amygdalina - Al-deeb, Ibrahim; Julia Joseph; Amin Malik Shah Abdul Majid; Aman Shah Abdul Majid; Nozlena Abdul Samad (Penerbit Universiti Kebangsaan Malaysia, 2022)
Angiogenesis is the process of generating new blood vessels that deliver tumor cells with oxygen and essential nutrients for growth and metastasis. This study examined the in vitro antiangiogenic properties of the ethanolic crude extract from Vernonia amygdalina (VA) grown in Malaysia. The direct antiangiogenic activity of VA was evaluated on EA.hy926 cells using in vitro assessments: Cell proliferation, colony formation, migration, and cell invasion assays. VA ethanolic crude extract cytotoxic activity was evident in the antiproliferative and colony formation assays. The growth inhibition (IC50) of 50% against EA.hy926 endothelial cells was achieved after 72 h treatment at a concentration of 85.43±3.57 μg/mL. Upon 48 h treatment, colony formation was inhibited completely at 100 μg/mL while 51.94% inhibition was achieved at 50 μg/mL. Moreover, the extract showed 54.72% and 31.99% inhibitory effects against migration of cells when treated for 24 h treatment at two different concentrations, 25 μg/mL and 12.5 μg/mL, respectively. The use of 100 μg/mL VA ethanolic extract inhibited cell invasion by 35.43%, which was lower than that of 57.81% inhibition achieved by the vinblastine as a positive control. All in all, the present work clearly demonstrated the antiangiogenic properties of VA ethanolic extract that may reflect a chemotherapeutic and/or chemoprevention potential for biomedical applications.